Microbial Inoculation Technology of Legume Seed for Crop Improvement - Monalisha, S P (International Journal of Psychosocial Rehabilitation, 2025)
The most well-researched biological nitrogen fixation mechanism is the rhizobia-legume symbiosis. Practically accepted measures to improve the quality of legume body are now the treatment of vegetable seeds with rhizobia. However, due to the low rates of live rhizopia in these products, the effectiveness of certain commercial inoculants cannot be guaranteed in China. A greenhouse experiment was performed to evaluate the effects on alfalfa productivity and nitrogen fixation of various rhizobial inoculant formulations. The use of beneficial microorganisms as alternatives to chemical pesticides and synthetic fertiliser in agricultural production is becoming progressively important. Application of beneficial microorganisms to seeds is an effective method for putting microbial inocula in soil where seedling roots are colonized and protected from insect or soil diseases. The use of beneficial microorganisms as alternatives to chemical pesticides and synthetic fertiliser in agricultural production is becoming progressively important. In view of the long history of Rhizobia spp. inoculation of leguminous plants, there are still very few commercially available microbial seed inoculants and simple laboratory demonstrations of the ability of a wide variety of other beneficial microorganisms to improve crop efficiency. The application of effective rhizobia to the soil and later the rhizosphere of legumes is an efficient and convenient way to inoculate leguminous seed. Nevertheless, its potential is yet to be understood very well. The introduction of high-quality inoculants revolutionized legumes technology in Australia in the 1960s following the widespread collapse in crops.